Analisis Kepatuhan Laporan Keuangan Koperasi Berdasarkan SAK ETAP - Nia Yuniarsih (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
The objective of this research is to describe the compliance annual report Koperasi Sekar Melati IBI Kota Surabaya with Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP). Operational definition this research to measure compliance are components of Financial Statements, Recognition, Measurement, Balance Sheet Account’s, Income Statement Account’s, Statement of Equity Exchange Account’s, Cash Flow Statement Account’s. The research method using descriptive analysis. The sampling technique used documentation of the Annual Financial Statement of Koperasi Sekar Melati IBI Kota Surabaya ended year 2015. The results of this study indicate that the Financial Statements Koperasi Sekar Melati IBI Kota Surabaya still not comply with the SAK ETAP.